2004
DOI: 10.1111/j.1365-2141.2004.05205.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of protein gene product 9·5 (PGP9·5)/ubiquitin‐C‐terminal hydrolase 1 (UCHL‐1) in human myeloma cells

Abstract: Summary The neuron cytoplasmic protein gene product 9·5 (PGP9·5)/ubiquitin‐C‐terminal hydrolase 1 (UCHL‐1) protein is a thiol protease that recognizes and hydrolyzes a peptide bond at the C‐terminal of ubiquitin, and is involved in the processing of ubiquitin precursors and ubiquinated proteins. Although this molecule is known as a specific tissue marker for the neuroendocrine system, many reports have indicated that PGP9·5 is a marker for certain tumour types, such as cancer of the lung, colon, and pancreas. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 28 publications
1
28
0
Order By: Relevance
“…as the cause of transformation. (19)(20)(21)(22)(23)(24)(25)(26)(27) Although PGP9.5 is known to be a dual function protein, that is, as a hydrolase to generate free ubiquitin and as a ligase to produce multi-ubiquitin chains, (17,41) both activities are involved in regulating ubiquitin levels. Moreover, the accumulation of ubiquitin has been documented in various types of primary cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…as the cause of transformation. (19)(20)(21)(22)(23)(24)(25)(26)(27) Although PGP9.5 is known to be a dual function protein, that is, as a hydrolase to generate free ubiquitin and as a ligase to produce multi-ubiquitin chains, (17,41) both activities are involved in regulating ubiquitin levels. Moreover, the accumulation of ubiquitin has been documented in various types of primary cancers.…”
Section: Discussionmentioning
confidence: 99%
“…medullary thyroid carcinoma, (24) ESCC, (25) myeloma (26) and neuroblastoma. (27) Interestingly, a previous methylation analysis of the promoter region of PGP9.5 showed that a virtual absence of methylated CpG sites in lung cancer cell lines is consistent with relatively high PGP9.5 expression, and that dense methylation contributes to the lack of its expression in HeLa cells, (28) suggesting that PGP9.5 expression is regulated by promoter methylation.…”
mentioning
confidence: 99%
“…Whole cell lysates from drug-treated MT-2 cells were made with lysis buffer (50 mM Tris-HCl (pH 7.2), 150 mM NaCl, 1% Nonidet P-40, 1% deoxycholate and 0.05% SDS) supplemented with protease inhibitor (Sigma-Aldrich Japan Inc., Tokyo, Japan,) as reported previously [21,22]. Soluble fractions were boiled in 1 × SDS loading buffer before electrophoresis.…”
Section: Western Blottingmentioning
confidence: 99%
“…Deletion of Uchl1 in mice leads to a fatal neurodegenerative disorder known as gracile axonal dystrophy (4), and mutations have been identified that impact the pathogenesis of Parkinson's disease (5,6). Expression outside neuroendocrine tissues is found in various cancers, including B cell lymphoma (7), multiple myeloma (2,8), and lung cancer (9). Using transgenic (Tg) mice, we demonstrated that UCH-L1 is in fact an oncogene that causes the same malignancies, most likely by boosting Akt signaling (2).…”
mentioning
confidence: 99%